A rapid and efficient solvent-free microwave-assisted synthesis of pyrazolone derivatives containing substituted isoxazole ring. Issue 22 (2nd June 2016) - Zhang, Dawei; Zhang, Yumin; Zhao, Tianqi; Li, Jing; Hou, Yaya; Gu, Qiang
Abstract: An efficient synthesis of 4-substituted pyrazolone derivatives was developed. 4-Substituted pyrazolone derivatives were synthesized in 78–97% yields starting from various 3-substituted isoxazole-5-carbaldehydes, ethyl acetoacetate and hydrazine under microwave irradiation and solvent-free conditions, and were characterized by HRMS, FTIR, 1 H NMR and 13 C NMR spectroscopy. SiO2 was found to possess favorable catalytic activity and dispersancy for the condensation reaction. The merits of this method include the environmentally friendly reaction conditions, simple operation, broad substrate, satisfied yields and the reuse of the silica. Moreover, the crystal structure of the compound 2-(4-chlorophenyl)-4-((1-(4-chlorophenyl)-5-hydroxy-3-methyl-1 H -pyrazol-4-yl)(3-phenylisoxazol-5-yl)methyl)-5-methyl-1 H -pyrazol-3(2 H )-one (5a ) in the monoclinic space group C2/c was presented. Graphical abstract: An efficient synthesis of 4-substituted pyrazolone derivatives was developed via condensation starting from ethylacetoacetate, hydrazine and isoxazole-aldehyde over solid support SiO2 under microwave-assisted solvent-free conditions in satisfactory yields.